Quality of life and living standards analysis : an econometric approach - Aĭvazi͡an, S. A. (Sergeĭ Artemʹevich) (Walter de Gruyter, 2016)
This book is about the concept of "Quality of Life". What is necessary for quality of life, and how can it be measured? The approach is a multicriterial scheme reduction which prevents as much information loss as possible when shifting from the set of partial criteria to their convolution. This book is written for researchers, analysts and graduate and postgraduate students of mathematics and economics.